Case reportTwo different ischaemic heart entities with the same clinical presentation - Zdravkovic, Vladimir; Vucic, Rada; Lazic, Zorica; Iric-Cupic, Violeta; Jovic, Marina; Davidovic, Goran; Zdravkovic, Nemanja (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
In this article we report two patients with different ischaemic heart entities who had sustained chest pain and showed numerous abnormal electrocardiograms (ECGs). To our knowledge, this is a very important report for the differential diagnosis of acute coronary syndrome and hypertrophic cardiomyopathy, which may give almost identical clinical presentation, ECGs and laboratory findings, making coronarography necessary for final diagnosis.